PENGARUH PROFITABILTAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN JASA SUB SEKTOR TRANSPORTASI PERIODE 2018-2022 - Fahira, Andi Nurul; Nurwahyuni, Nurwahyuni; Ikhtiari, Kirana (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
This study aims to assess the impact of profitability and liquidity ratios on firm value within the transportation service sector. The research adopts a quantitative approach, utilizing secondary data sourced from financial reports obtained from https://www.idx.co.id/id and official company websites. The study focuses on transportation companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022, with a purposive sample size of 135 data points. The analytical method employed is multiple linear regression analysis. The findings suggest that profitability ratios, tested through hypothesis testing, exhibit a positive but statistically insignificant influence on firm value. This implies that changes in profitability ratios, whether positive or negative, do not significantly affect firm value. Conversely, liquidity ratios demonstrate a positive and statistically significant impact on firm value, indicating that variations in liquidity ratios do influence firm value. In conclusion, the study indicates that while profitability ratios do not exert a significant influence on firm value in the transportation sector, liquidity ratios are instrumental in shaping firm value.